2019
DOI: 10.1038/s41590-019-0493-z
|View full text |Cite
|
Sign up to set email alerts
|

House dust mites activate nociceptor–mast cell clusters to drive type 2 skin inflammation

Abstract: # The following authors contributed equally Life Sciences Reporting Summary. Further information on experimental design and reagents is available in the Life Sciences Reporting Summary. Data availability. The data that support the findings of this study are available from the corresponding author Nicolas Gaudenzio upon request.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
245
3
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 247 publications
(253 citation statements)
references
References 52 publications
4
245
3
1
Order By: Relevance
“…In contrast to another report, we found that Alternaria extract, which has serine protease activity, was also capable of inducing DRG release of Substance P and inhibition of CGRP ( Fig. S1) (Cayrol et al, 2018;Serhan et al, 2019). These data indicate that the capacity for sensory neuron activation and Substance P release may be shared amongst disparate allergens.…”
Section: Substance P Release From Sensory Neurons Induces Cd301b + DCcontrasting
confidence: 99%
See 4 more Smart Citations
“…In contrast to another report, we found that Alternaria extract, which has serine protease activity, was also capable of inducing DRG release of Substance P and inhibition of CGRP ( Fig. S1) (Cayrol et al, 2018;Serhan et al, 2019). These data indicate that the capacity for sensory neuron activation and Substance P release may be shared amongst disparate allergens.…”
Section: Substance P Release From Sensory Neurons Induces Cd301b + DCcontrasting
confidence: 99%
“…Using potassium chloride (KCl) responsiveness as a marker of live neurons, we found that approximately 16% neurons were responsive to 5 papain ( Fig. 2C), a similar value to that reported for house dust mite responsive neurons (Serhan et al, 2019). TRPV1 expression defines a subset of nociceptive neurons that not only sense noxious heat, but also promote pruriceptive responses.…”
Section: Allergens Directly Activate a Population Of Sensory Neurons supporting
confidence: 76%
See 3 more Smart Citations